Leadership behavior of football coaches from the point of view of coaches of firstclass and excellent clubs in the governorates of Iraq - Sajjad kareem ghunaim (Global Scientific Publishing, 2023)
The research aims to identify: - -1The degree of preferred leadership behavior of the football coach - -2The type of differences in the degree of preferred behavior of a football coach and its dimensions between coaches of first-class and excellent clubs. The coach is considered one of the three most important elements in the field of sports (the coach, the player, and the training curriculum). Paying attention to his leadership behavior and understanding his answers to the vocabulary of the leadership scale are all important matters in describing the situation of our Iraqi coach. In view of the lack of specialized leadership behavior for football coaches, the researcher studied this subject. The aim of the research was to identify the degree of leadership behavior preferred by football coaches. The research sample consisted of (22) coaches. It was designed by (Shella duroi and Salah) 1980, and it was quoted by Muhammad Hassan Allawi, and it consists of (38) paragraphs that measure four dimensions of behavior. The researcher concluded the following: - -International class football coaches were distinguished by more autocratic behavior (authoritarian, dictatorial) compared to first class coaches. - -There are no significant differences between the first-class coaches and the second-class football coaches in the preferred leadership behavior in the items of the scale as a whole
Keywords: Leadership behaviour; First class coaches; the scale